Potret Kekerasan dalam Novel Perempuan Yang Menangis Kepada Bulan Hitam karya Dian Purnomo - Windy Septian; Yenni Hayati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to describe: (1) the forms of violence in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo, (2) the causes of violence in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo, (3) The impact of violence in the novel Woman who Weeps for the Black Moon by Dian Purnomo. The object of research used by researchers is the novel Woman Crying To The Black Moon by Dian Purnomo, which was published in 2020. In this study, a descriptive method was used. In collecting the data used in this study in the form of words, phrases, clauses, and sentences related to the forms, causes, and impacts of violence in Dian Purnomo's novel Women Crying To The Black Moon. The research instrument was the researchers themselves using the help of other instruments in the form of recording sheets. The data collection technique used was reading and understanding the novel, determining the main character, and searching for data and recording data related to the research problems contained in the novel. The data analysis technique used is to classify the data then interpret the data, and conclude the data analysis. The results of this study are as follows. First, the forms of violence in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo are divided into physical violence in the form of slapping, grabbing and hitting, psychological violence in the form of yelling and insults, and sexual violence in the form of forced kisses. and forced intercourse. Second, the causes of violence in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo are divided into two factors, namely internal factors and external factors. The three impacts of violence in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo are physical impacts in the form of severe injuries and bruises and non-physical effects in the form of depression and mental disorders.